OPTIMALISASI JARAK PEMASANGAN PREFABRICATED VERTICAL DRAIN (PVD) DALAM POLA PERSEGI PADA PERBAIKAN TANAH LUNAK - Sofya Marinda Putri Wilis; Agata Iwan Candra; Fauzie Nursandah (LPPM Universitas Abdurrab, 2024)
Abstract Due the construction phase in project of the Dhoho Kediri International Airport Toll Road at STA 7+000 – STA 7+100 mentioned soft soil, leading to significant and time-consuming consolidation. In an effort to expedite the consolidation process, the preloading method with Prefabricated Vertical Drain (PVD) is applied. This method includes backfilling plan and PVD installation to reduce the flow of pore water in the soil, allowing for faster consolidation. This research aims to enhance the effectiveness of soil improvement by evaluating the influence of PVD installation distances in a square pattern. The research focuses on the analysis of soil parameters and PVD installation at distances ranging from 1.1m to 1.7m. The results indicate that the installation of square-patterned PVD is effective in accelerating consolidation. The final settlement prediction using the Terzaghi One-Dimensional approach provides practical references. Simulation results for distances between 1.1m and 1.7m show that 1.1m is the most effective distance because closer PVD installations result in faster consolidation times. This is evidenced by the consolidation time comparison, where without PVD, it takes 51,92 years to achieve 90% consolidation, while with PVD, it only requires 144 days. These findings are expected to provide practical guidance and significant contributions to the design of soil improvement in similar toll road construction projects. Keywords: Distance, Consolidation, Prefabricated Vertical Drain, Square pattern, Preloading.